Lymphopenia With Clinical and Laboratory Features of Combined Immune Deficiency in an 11-Year-Old Female With FANCD2 Variants and Fanconi Anemia - Deniskin, Roman; Sasa, Ghadir S.; Nandiwada, Sarada L.; Rider, Nicholas L. (Frontiers in Pediatrics, 2019)
Fanconi anemia (FA) is an inherited bone marrow failure and cancer predisposition disorder due to mutations in DNA repair pathways proteins (FANC). The dysfunctional proteins are unable to repair DNA breaks and cause genomic instability. Mutations in many of the 19 FANC genes are well characterized biochemically and clinically. Little is known about the FANCD2 gene which acts downstream of the FA-core proteins. Here we report a 11-year-old female previously diagnosed with FA and bone marrow failure. Gene sequencing demonstrated deletion of exons 2-18 and a pathologic missense mutation (c. 2444G>A, p. Arg815Gln) in FANCD2 (Chr3). Her medical history is significant for an episode of pneumococcal sepsis despite adequate vaccination. Repeated blood samples and immunophenotyping demonstrated severe lymphopenia. There were markedly low CD4+ T-cell counts with a low CD4:CD8 ratio. Changes in the composition of the B-cell population included significantly diminished absolute total B-cells, and decreased mature cells. There was no immunogenic response to vaccination against S. pneumoniae. The NK-cell count was unaffected and demonstrated normal spontaneous and stimulated cytotoxic response. Bone marrow analysis demonstrated hypocellularity without dysplasia. The clinical and laboratory features are suggestive of combined immune deficiency. FANCD2 may be involved in the transition of immature B and T cells to mature cells, a process that requires substantial DNA recombination not observed in NK cells. Additional genetic and biochemical evaluation is needed to further characterize the novel genetic and clinical findings.